Thin Film Structures in Energy Applications - Babu Krishna Moorthy, Suresh.; Babu Krishna Moorthy, Suresh. (Springer International Publishing : Imprint: Springer, 2015)
This book provides a comprehensive overview of thin film structures in energy applications. Each chapter contains both fundamentals principles for each thin film structure as well as the relevant energy application technologies. The authors cover thin films for a variety of energy sectors  including inorganic and organic solar cells, DSSCs, solid oxide fuel cells, thermoelectrics, phosphors and cutting tools.